Ferramentas 3D como auxílio no processo de ensino-aprendizagem na disciplina de anatomia - (:unkn) unknown (Universidade Brasil, 2021)
The study of the discipline of anatomy requires from the student a high capacity for attention and concentration in order to achieve learning in its entirety, becoming a laborious and strenuous process due to its intricate richness of details. This factor is associated with the high use of an anatomical organic demand that degrades with significant speed and requires constant replacement or use of toxic chemicals for longer use. The objective of this work is to investigate the benefits in terms of learning anatomy with the aid of 3D tools. Images of organs for 3D screen were developed, as well as the impression of organs in polymeric resin for use in the classroom. Forty students aged between 18 and 60 years old of both sexes were evaluated, all belonging to the same institution of technical education in nursing. The study was based on 2 groups of students: the first class (n = 20) received the content and application of the anatomy discipline through books, illustrations, blackboard and slide projection. The second class (n = 20) received the same information content as the first, taught by the same teacher, using traditional resources, with the addition of 3D projection screens and pieces printed on a 3D printer. The analysis took place in both classes through a content review class, carried out between the application of a first questionnaire (entry questionnaire), and a second verification questionnaire after the review class (exit questionnaire). The questionnaire covered the following domains: proportion, spatial location, volumetry, morphology, similarity and motivation. The results confirmed the effectiveness of the proposed model using 3D when observing the domains of spatial location/physical anatomy, volumetry/planaltimetry and motivation when compared to the class that used 3D resources with the control group, of traditional methodology. It was also possible to validate the use of 3D impressions, as well as the use of multi-auto-stereoscopic (3D) images, their inherent depth perception, in addition to justifying the gradual entry of practical, perennial and detailed technologies, as they allow the reduction of perishable organs and corpses, as well as the dangerous contact with toxic chemicals in educational environments.
Keywords: Tecnologia; Ensino 3D; Anatomia; Processo de ensino-aprendizagem; Bioengenharia; CS